2003
DOI: 10.1007/978-94-010-0093-2_30
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of the Hudson Apron Slope, Off New Jersey, U.S.A.

Abstract: As part of the STRA T AFROM project, the Hudson Apron area was selected for a detailed slope stability analysis. Results indicate that high pore pressure is necessary to trigger a failure. Under normal conditions, an excess pore pressure of more than 90% would be required for failure. On the other end, the actual strength profile would indicate a remaining marginal stability. Aggravating factors were the high sedimentation rate cyclicity and resulting layering inducing high excess pore pressures, and potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…An analysis of the geomechanical or geotechnical properties of sediments is paramount in addressing the sediment's role in submarine failure (e.g. Locat et al, 2003a). For the Traenadjupet slide (Fig.…”
Section: Geomechanical Properties Of Sedimentsmentioning
confidence: 99%
“…An analysis of the geomechanical or geotechnical properties of sediments is paramount in addressing the sediment's role in submarine failure (e.g. Locat et al, 2003a). For the Traenadjupet slide (Fig.…”
Section: Geomechanical Properties Of Sedimentsmentioning
confidence: 99%
“…Factor of safety analysis (e.g., and ) of the slope during sedimentation and overpressure genesis predicted low factors of safety but did not successfully predict unstable conditions (FS < 1) [ Dugan and Flemings , 2002]. Sediment strength analyses coupled with stability modeling for the New England margin concluded that high overpressures and weak sediments are required to drive failures on such low‐angle slopes (<4°) and that the measured shear strength is consistent with marginal stability for the New England slope [ Locat et al , 2003]. Together the overpressure modeling and slope stability assessment successfully reproduce the regional overpressure profile and indicate that high overpressures are required to precondition the slope for repeated failures, such as those that were observed.…”
Section: Examples Of Overpressured Systemsmentioning
confidence: 99%
“…The New Jersey study area also showed evidence of mass movements. Locat et al (2003) conducted a geotechnical analysis of a failure on the Hudson Apron slope using results of testing on ODP cores (Austin et al, 1998;Dugan et al, 2002) and long Calypso piston cores. The analysis showed that high excess pore pressures were required to cause the failure and that they probably acted in the context of a layered system with groundwater seepage.…”
Section: Contributions To Submarine Landslide Research From the Strat...mentioning
confidence: 99%